Knowledge and attitude about pulmonary tuberculosis among community people of selected ward, Butwal. - Khatri, Renu (2018)
ABSTRACT: Tuberculosis (TB) is contagious and airborne disease caused by Mycobacterium tuberculosis. It comes under one of the top 10 causes of death worldwide. This quantitative descriptive cross-sectional study was carried out to find out the knowledge and attitude regarding pulmonary tuberculosis among community people. This study was carried out in Ward No. 7 Butwal Sub-metropolitan with sample size 128 by using non-probability purposive sampling technique. Data collection was done by face to face interview using self-developed structured questionnaires. The data were analyzed using descriptive and inferential statistics through the Statistical Package for Social Sciences (SPSS) version 23. The study revealed that the majority of respondents (65.6%) had inadequate, 30.5% had moderate and only 3.9% had adequate knowledge about pulmonary tuberculosis. Most of the respondents (89.1%) had a positive attitude toward PTB. Knowledge is statistically significant with educational status (p=0.014), income status (p=0.015) and heard or seen PTB patient in community (p=0.002) and attitude is associated with heard or seen PTB patient in community (p=0.048). The result of this study concluded that most of the respondents had inadequate knowledge and positive attitude about pulmonary tuberculosis. Therefore, the overall findings of this study suggest that periodical awareness program in the community should be strengthened including all aspects of PTB. Keywords: Attitude, Community people, Knowledge, Pulmonary tuberculosis